Perbandingan Pemikiran Tokoh Dalam Novel Dahlan dan Novel Penakluk Badai Serta Relevansinya Terhadap Pembelajaran Sastra Berbasis Karakter di SMA - Mudaksir Mudaksir; Juanda Juanda; Munirah Munirah (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to describe the differences and similarities in the thoughts of the characters in the novel Dahlan by Haidar Musyafa and the novel Penakluk Badai by Aguk Irawan MN and the relevance of novel analysis to literary learning materials in class XII high school. This research was a qualitative research. This study used a comparative literature approach with Damono's theory. The data collection techniques used in this study were documentation techniques, reading techniques, and note-taking techniques. Data were analyzed qualitatively with descriptive data presentation. The data were obtained through the literature study method. The data in this study were analyzed by describing the similarities and differences. The results of the study indicated the differences and similarities in the thoughts of the characters in the novel Dahlan and the novel Penakluk Badai and their relevance to literary learning materials in high school. The findings of this study on its relevance to literary learning in high school by including the story text in literary learning materials and as an example before students write a literary work.